Inaugural RAMP Survey on the Reserve Management Practices of Central Banks : Results and Observations - World Bank (World Bank, Washington, DC, 2019)
In the spring of 2018, the World Bank Treasury's Reserves Advisory and Management Program (RAMP) concluded its inaugural survey on central banks' reserve management practices. RAMP sought to assess whether there had been a significant evolution in this activity over the past two decades given: